The hippocampus of birds in a view of evolutionary connectomics. (September 2019) - Herold, Christina; Schlömer, Philipp; Mafoppa-Fomat, Isabelle; Mehlhorn, Julia; Amunts, Katrin; Axer, Markus
Abstract: The avian brain displays a different brain architecture compared to mammals. This has led the first pioneers of comparative neuroanatomy to wrong conclusions about bird brain evolution by assuming that the avian telencephalon is a hypertrophied striatum. Based on growing evidence from divers analysis demonstrating that most of the avian forebrain is pallial in nature, this view has substantially changed during the past decades. Further, birds show cognitive abilities comparable to or even exceeding those of some mammals, even without a "six-layered" cortex. Beside higher associative regions, most of these cognitive functions include the processing of information in the hippocampal formation (HF) that shares a homologue structure in birds and mammals. Here we show with 3D polarized light imaging (3D-PLI) that the HF of pigeons like the mammalian HF shows regional specializations along the anterior–posterior axis in connectivity. In addition, different levels of adult neurogenesis were observed in the subdivisions of the HF per se and in the most caudal regions pointing towards a functional specialization along the anterior–posterior axis. Taken together our results point to species specific morphologies but still conserved hippocampal characteristics of connectivity, cells and adult neurogenesis if compared to the mammalian situation. Here our data provides new aspects for the ongoing discussion on hippocampal evolution and mind.